What future for agriculture in the Pacific? - Setae, Miri (Technical Centre for Agricultural and Rural Cooperation, 1996)
What future for agriculture in the Pacific?Miri Setae was lecturer at Vudal Agricultural College, Papua New Guinea before becoming Livestock Development Officer forMorobe Province and then Provincial Rural Development Officer, East Sepik Province....